Mapuche Education and School Education in Araucanía: A Dual Educational Rationality? [Éducation Mapuche Et Education Scolaire À Araucania: Une Double Rationalité Éducationnelle?] [Educação Mapuche E Educação Escolar Na Araucania: Dupla Racionalidade Educacional?] [Educación Mapuche y Educación Escolar en la Araucanía: ¿Doble Racionalidad Educativa?] - Loncon-Antileo, E (Fundacao Carlos Chagas, 2016)
This article discusses the social construction of a double rationality in the Mapuche educational knowledge. The framework refers to an epistemic base of the Mapuche educational knowledge and the notion of the relation to knowledge in which the equation embodied past and present action context equals observable practices. The methodology raises an epistemological critique of the traditional research among indigenous peoples. The results summarize the main features of dual immersion education of children and young Mapuche based on their parents’ speeches. This article concludes that Mapuche education is grounded on a double educational rationality to overcome the monolingual-monocultural Chilean school curriculum. © 2016, Fundacao Carlos Chagas. All rights reserved.